2015
DOI: 10.1128/aem.00067-15
|View full text |Cite
|
Sign up to set email alerts
|

C/N Ratio Drives Soil Actinobacterial Cellobiohydrolase Gene Diversity

Abstract: dCellulose accounts for approximately half of photosynthesis-fixed carbon; however, the ecology of its degradation in soil is still relatively poorly understood. The role of actinobacteria in cellulose degradation has not been extensively investigated despite their abundance in soil and known cellulose degradation capability. Here, the diversity and abundance of the actinobacterial glycoside hydrolase family 48 (cellobiohydrolase) gene in soils from three paired pasture-woodland sites were determined by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 73 publications
(96 reference statements)
4
23
0
Order By: Relevance
“…For example, an increase of the proportion of Proteobacteria in this study could give rise to increase of Azotobacteria, while a decrease of the proportion of Actinobacteria could result in reduction of metabolic active substances released by it and related to the promotion of plant growth. Some study results showed that Actinobacteria presented a significant correlation with soil organic matter content or C:N ratio, so the reduction of Actinobacteria might be caused by the increase of soil organic matter [50,51]. However, variation tendencies of bacterial diversity indexes in all treatments were not obvious, and the change of bacterial phylum was also small, which indicated that compost application cannot significantly affect microbial diversity and increase hazardous microorganisms after fertilization.…”
Section: Discussionmentioning
confidence: 97%
“…For example, an increase of the proportion of Proteobacteria in this study could give rise to increase of Azotobacteria, while a decrease of the proportion of Actinobacteria could result in reduction of metabolic active substances released by it and related to the promotion of plant growth. Some study results showed that Actinobacteria presented a significant correlation with soil organic matter content or C:N ratio, so the reduction of Actinobacteria might be caused by the increase of soil organic matter [50,51]. However, variation tendencies of bacterial diversity indexes in all treatments were not obvious, and the change of bacterial phylum was also small, which indicated that compost application cannot significantly affect microbial diversity and increase hazardous microorganisms after fertilization.…”
Section: Discussionmentioning
confidence: 97%
“…The ecology and distribution of each of these phyla reflects the combined ecological and biogeographic characteristics of all the genera in that phylum. Members of Actinobacteria are known to have an important role in organic matter turnover and the breakdown of recalcitrant molecules, such as cellulose and complex hydrocarbons, and are particularly abundant in woodland soils where the C/N ratio is highest ( 48 ). In our data set, the genera Frigoribacterium , Acidothermus , Conexibacter , and Mycobacterium were more abundant in forests or correlated with a high C/N ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Proteobacteria found in our study is similar to the reported in other soil studies (Castañeda & Barbosa, 2017). Actinobacteria also participates actively in the terrestrial carbon cycling through organic matter turnover, breakdown of recalcitrant molecules and production of secondary metabolites (de Menezes et al, 2015). Interestingly, a higher relative abundance of Bacteroidetes was found in Cq compared to Cq+Da samples (19.08% and 13.53%, respectively); Bacteroidetes are involved in degradation of plant material and related organic molecules such as starch and cellulose (Aislabie et al, 2013) and their abundance correlates with soil pH, available nitrogen/phosphorus content and water content (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%